Evaluation of Some Hematological Parameters for Patients Infected with Entamoeba Histolytica in Najaf Governorate: Evaluasi Beberapa Parameter Hematologi untuk Pasien yang Terinfeksi dengan Entamoeba Histolytica di Kegubernuran Najaf - Ibtesam Mohsen Al-Azawe; Hawraa Mohammed Al-ali; Rabab Ali Al-Mosawi (Universitas Muhammadiyah Sidoarjo, 2024)
General background: Amoebic dysentery caused by Entamoeba histolytica is a significant public health concern, particularly in regions with poor sanitation. It can lead to various complications, including changes in blood parameters. Specific background: Identifying changes in blood indicators during amoebic infections can aid early diagnosis and improve patient outcomes. Knowledge gap: There is limited research exploring gender-based differences in blood parameters of patients with amoebiasis. Aims: This study aimed to evaluate the effect of E. histolytica infection on specific blood parameters in male and female patients and to assess gender-based variations in these parameters. Results: A total of 45 patients (20 males, 25 females) diagnosed with amoebiasis were included, with samples collected between May 2023 and January 2024. Significant differences (P ≤ 0.05) were observed between male and female patients in RBC, HB, HCT, and MCH, while no significant differences were noted for MCV, MCHC, RDW, PLT, WBC, or LYM. Male patients showed higher mean values of RBC (5.01 ± 0.65) and HB (14.6 ± 1.61) compared to females (RBC: 4.5 ± 0.54; HB: 12.28 ± 1.24). Novelty: This study highlights gender-specific alterations in blood parameters during amoebiasis, providing new insights into how gender affects physiological responses to E. histolytica infection. Implications: Regular monitoring of blood parameters, particularly RBC and HB, in patients with amoebiasis is crucial for early diagnosis and treatment. The findings also underscore the importance of gender considerations in clinical management and suggest the need for larger studies to confirm these results and explore their diagnostic and therapeutic implications. Highlights: Gender impacts blood parameters in amoebiasis patients. Males show higher RBC and HB than females. Regular monitoring aids early E. histolytica diagnosis. Keywords: Amoebic dysentery, Entamoeba histolytica, blood parameters, gender differences, early diagnosis